Approaches to PAI Curriculum Development - Irma Nur Afifah; Virda Nailatul Iza; Septia Nur Laili; Mohammad Yahya (Jurnal Pengabdian Nusantara, 2026)
This study discusses various approaches used in the development of the Islamic Education Curriculum (PAI) and its urgency in improving the quality of learning. The purpose of this study is to identify the characteristics, advantages, and relevance of each approach to the needs of contemporary Islamic education. The research method used is a literature study with descriptive analysis of the literature related to the development of the PAI curriculum. The results of the study show that there are five main approaches in the development of the PAI curriculum, namely the academic subject approach, humanistic approach, technological approach, social reconstruction approach, and competency-based approach. These approaches are considered to be able to serve as a basis for educators in designing a more meaningful and contextual curriculum. The existence of the PAI curriculum plays a strategic role as a guideline for achieving the goals of Islamic education, namely exploring human potential in accordance with Islamic law. However, the PAI curriculum still faces various problems, such as monotonous learning models, overlapping material, and a lack of relevance to the social context of students. Therefore, the selection and combination of the right approaches is very important so that the PAI curriculum can be implemented effectively and adaptively in the teaching and learning process.